A new allele of the duplicated 27kD zein locus of maize generated by homologous recombination. - Das, O P (1991)
The 27kD zein storage protein locus in many inbred lines of maize consists of a tandem duplication of 12kb, with an expressed gene in each repeat, termed A and B. A single-copy allele with only the A gene can be generated from this duplication in particular stocks of the maize inbred line A188 by a mitotic process that includes a crossover at the 3' regions of the two genes (1). Here, we characterize a second single-copy allele with only the B gene, found in different stocks of A188. This allele arises from a homologous recombination at the highly conserved 5' regions of the two repeats, and cloning and sequencing of this allele define the crossover region. The A and B genes in the duplicated allele were previously shown to be expressed at different levels; this difference remains unchanged in either recombinant allele. Therefore, the crossover points of these two recombinant alleles define the borders of cis-acting sequences responsible for the differential expression of the two genes.